Signification of Filipino culture in the film RPG Metanoia - Asuncion, April Angeli B; Limjuco, Ivan Christian V. (2014.)
This study identifies and describes the different significations of Filipino Culture in the 3D animated film RPG Metanoia. It is supported by Semiotics? basic claim that media texts are made up of signs, which are composed of two elements: the signifiers and the signified. The signifier is the physical representation of a sign that is being perceived by the senses, while the signified are the meanings that are being associated with the sign. The signifiers in this study are the different physical representations of the different Components of Culture according to Panopio et al. (1978) namely, Norms, Ideas and Material Culture. Data were gathered through observation and were further analyzed using content analysis. An interview with creators of the film was also conducted. Results show that the different significations of Filipino Culture in the film are Norms like Barkada System and Kwentuhan, Ideas which include the value of Pagkamasayahin and Belief in the Supernatural, and Material Culture which is signified by Filipino Clothing.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Signification; Signified; Signifier; Filipino Culture; Culture, Components; Norms; Ideas; Material Culture; Pinano, Von Janatius A; Zante, Sheena Angelique D